Telaah Ulang Hak Paksa dalam Perkawinan Islam melalui Pendekatan Fiqh, Munâsib al-‘Illah dan ‘Urf - Moh. Dliya'ul Chaq (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2017)
The provision ijbâr Rights in Islam has become the legal umbrella of forced marriage implementation in a deep-rooted society. The existence of unbalanced understanding and strong indication of the influence of ‘urf. Through fiqh approach, munâsib al-‘illah and ‘urf focusing on review of forced reextrictions in Islamic law, obtained that right ijbâr is actually a safeguard against girls but when it becomes a guardian’s right, it can not be applied because; right of girl in the fiqh salaf takes precedence over the right of guardians as the provisions of guardians ‘ad}al and the requirements of the guardian of mujbîr; legal images of the nature of girl and nature of children in the study of munâsib al-‘illah with the approach of al-qawâ’id al-fiqhîyah has one point of similarity that ‘illat is immature in sense of not being able to determine mas?lah?ah herself that shows maqâs}id avoids girls from danger, and this is difficult to achieve by forced marriage; the basic law of the right of ijbâr is the hadith that ‘illat in hadith it is ‘urf so that the hadith’s validity depends on ‘urf; and deliberation between guardians and girls is the best and praiseworthy way of determining a potential mate.